ФОРМУВАННЯ ЛОГІЧНОЇ КУЛЬТУРИ СТАРШОКЛАСНИКІВ ПРИ ВИВЧЕННІ ІНФОРМАТИКИ (Педагогіка вищої та середньої школи, 2004)
In this article opened the system of educational exercises on development of logic culture of senior pupils at lessons of computer science.